Atomically sharp domain walls in an antiferromagnet - Krizek, Filip; Reimers, Sonka; Kašpar, Zdeněk; Marmodoro, Alberto; Michalička, Jan; Man, Ondřej; Edström, Alexander; Amin, Oliver J.; Edmonds, Kevin W.; Campion, Richard P.; Maccherozzi, Francesco; Dhesi, Samjeet S.; et al. (Science advances, 2022)
The interest in understanding scaling limits of magnetic textures such as domain walls spans the entire field of magnetism from its physical fundamentals to applications in information technologies. Here, we explore antiferromagnetic CuMnAs in which imaging by x-ray photoemission reveals the presence of magnetic textures down to nanoscale, reaching the detection limit of this established microscopy in antiferromagnets. We achieve atomic resolution by using differential phase-contrast imaging within aberration-corrected scanning transmission electron microscopy. We identify abrupt domain walls in the antiferromagnetic film corresponding to the Néel order reversal between two neighboring atomic planes. Our work stimulates research of magnetic textures at the ultimate atomic scale and sheds light on electrical and ultrafast optical antiferromagnetic devices with magnetic field–insensitive neuromorphic functionalities. Transmission electron microscopy reveals atomically sharp domain walls in a workhorse material of antiferromagnetic spintronics.